A Genealogy of the Author: The Emergence and Functioning of Modern Authorship - Morato de Andrade, Otávio (Sofia, 2025)
What does it mean to be an author? To create, to sign, to own? Often, we take the figure of the author as something constant, as if it has always existed throughout different eras and contexts. Philosopher Marco Antônio Sousa Alves shows us that we are dealing with a broader phenomenon: the authorial figure gradually emerged over the centuries, shaped by power structures, mechanisms of exclusion, and economic regulation. Alves’ book, A Genealogy of the Author: The Emergence and Functioning of Modern Authorship (Editora UFMG, 2021, 478 pages), traces the origins of this dynamic and fluid phenomenon, questioning what it is - and, just as importantly, how it emerged and how the author we know today functions.